A COMPARATIVE STUDY ON THE EFFICACY OF THREE GALENIC PREPARATIONS FOR TOPICAL USE - Brunilda Basha; Ledjan Malaj; Elton Myftari; Ermira Vasili (European Scientific Journal, ESJ, 2015)
Background: Atopic dermatitis, eczema, psoriasis are an important challenge for dermatology doctors. In order to have the best result in shorter time of treatment, it is necessary a collaboration with clinical pharmacists to have the right product, for the right type of skin, in the right amount according to the affected surface. It is very important to decide first which NSAID to use as topical therapy, second the type of formulation to use having at disposal Galenic preparations such as lotion, cream and unguent Objective: To study the efficacy and compliance of patients on three Galenic preparations. Method: A randomized, open group controlled trial. 198 patients were included in this trial to be treated either with lotion of 0.1%, cream of 0.1% or unguent 0.1% mometasone furoate (MF). The data were analyzed with chi-square test. Results: About 118 (59.6%) of patients were males and 80 (40.4%) were females. The male/female ratio was 1:0.67. After 28 days of treatment quite all patients were improved or had no signs of illness (lotion 97.6% improved, cream 80% absence of signs, unguent 63.0 % improved). The results after statistical analysis shows that there are much more possibility to become absent from signs using cream, rather than lotion or unguent [cream vs lotion 157 folds (P= 0.002) while unguent vs lotion 25 folds (P<0.001)]. There were not noticed any treatment-related irritation from all three formulations. Conclusion: All three formulations can improve the health status of patients with eczema, dermatitis or psoriasis. However cream gives faster and better clinical improvements compared to unguent or lotion. All three galenic preparations were well tolerated.